Trends in population-based incidence, diagnostics, and mortality of acute superior mesenteric artery occlusion - Soltanzadeh-Naderi, Y.; Acosta, S. (Frontiers in Surgery, 2024)
Acute occlusion of the superior mesenteric artery (SMA) results in lethal intestinal ischemia. Results from two previous population-based studies in Malmö, Sweden, suggest a decreasing incidence of acute SMA occlusion. The study aim was to evaluate trends of the epidemiology of acute SMA occlusion in Malmö. The report was a retrospective population-based study during 2014-2019 on patients with acute SMA occlusion residing in Malmö municipality. Patients were retrieved from Skåne University Hospital and post-mortem examinations. Epidemiological data was compared to one of the two studies, that one from 2000-2006. Sixteen patients with acute SMA occlusion resided in Malmö municipality. The incidence of acute SMA occlusion significantly decreased from 5.4/100,000 person-years to 0.8/100,000 person-years. The ratio of acute SMA occlusion to non-occlusive mesenteric ischemia (NOMI) decreased from 12.5:1 to 0.9:1 (p<0.0001), the proportion of inhabitants aged 80 or above in the population decreased from 6.0% to 4.3% (p<0.0001), and the autopsy rates decreased from 25% to 14% (p<0.0001). In-hospital mortality decreased from 63% to 44% (p=0.14). The incidence of acute SMA occlusion seems to be significantly decreased in Malmö probably due to high-resolution computed tomography angiographies around-theclock distinguishing acute SMA occlusion from NOMI, lowered share of elderlies, improved medical risk factor control, and lowered autopsy rate.